1978
DOI: 10.1113/jphysiol.1978.sp012498
|View full text |Cite
|
Sign up to set email alerts
|

The physiological effects of monocular deprivation and their reversal in the monkey's visual cortex.

Abstract: SUMMARY1. 1127 single units were recorded during oblique penetrations in area 17 of one normal, three monocularly deprived and four reverse sutured monkeys.2. In all animals most cells outside layer IVc were orientation-selective, and preferred orientation usually shifted from cell to cell in a regular progressive sequence.3. The presence in layer IV c of non-oriented, monocularly driven units, organized in alternating right-eye and left-eye 'stripes' (LeVay, Hubel & Wiesel, 1975) was confirmed.4. Early monocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(123 citation statements)
references
References 50 publications
8
115
0
Order By: Relevance
“…From these and similar experiments by us 13 , 15 and others 14,27 we conclude that the macaque monkey is highly susceptible to monocular deprivation during the first six weeks of life, at which age the sensitivity declines progressively, so that at 1½ to 2 years the monkey loses this type of neural plasticity. The length of the critical period varies between species.…”
Section: The Critical Periodmentioning
confidence: 88%
See 1 more Smart Citation
“…From these and similar experiments by us 13 , 15 and others 14,27 we conclude that the macaque monkey is highly susceptible to monocular deprivation during the first six weeks of life, at which age the sensitivity declines progressively, so that at 1½ to 2 years the monkey loses this type of neural plasticity. The length of the critical period varies between species.…”
Section: The Critical Periodmentioning
confidence: 88%
“…10 we showed that the monkey was also susceptible to visual deprivation, 11 a finding subsequently confirmed and extended. 12,13,14,15 Further advances in our understanding of the nature of and mechanism underlying the deprivation phenomena depended on working out some of the functional architecture of the visual cortex. This was done through further physiological experiments in the normal animal and by using newly developed anatomical methods.…”
Section: ´4mentioning
confidence: 99%
“…These findings establish 7 d of early MD in mice as a useful protocol to investigate strategies for reversing ocular dominance plasticity and promoting recovery from amblyopia. It has been known for many years from work in kittens and monkeys that deprivation-induced synaptic depression can be reversed if normal vision is restored in the weak (amblyopic) eye and the fellow eye is occluded (11,12). However, gains in the amblyopic eye often come at the expense of vision in the fellow eye, may be temporary, and are rarely accompanied by improvement in binocularity (9,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…This "reverse occlusion" approach has been validated in animals (11,12) and represents the cornerstone of current treatment (patching therapy) of human amblyopia (13)(14)(15)(16). However, this treatment has well-known limitations that include poor compliance, potential loss of vision through the newly patched eye, failure to recover binocular vision, and a declining treatment efficacy with age (15,(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The extent to which the initial effects of deprivation can be reversed and the speed of the changes depend upon the age at which reverse occlusion begins (Blakemore & Van Sluyters 1974;Movshon 1976a;Blakemore et al 1978Blakemore et al , 1981. Indeed, it has been argued that the temporal profile of the declining ability to reverse prior deprivation-induced effects represents a separate critical period for recovery (Daw 1998(Daw , 2002(Daw , 2003Lewis & Maurer 2005).…”
Section: Key Findings and Concepts Derived From Early Animal Studies mentioning
confidence: 99%